Advancement of lithium-ion battery cells voltage equalization techniques: A review. (December 2020) - Das, Utpal Kumar; Shrivastava, Prashant; Tey, Kok Soon; Bin Idris, Mohd Yamani Idna; Mekhilef, Saad; Jamei, Elmira; Seyedmahmoudian, Mehdi; Stojcevski, Alex
Abstract: Recently, the use of electric batteries has reached great heights due to the invention of electric vehicles (EVs). Many lithium-ion battery cells are usually connected in series to meet the voltage requirements. The voltages of the entire series-connected battery cells in a battery pack should be equal. However, such result is impossible due to some unavoidable reasons in real life. Unbalanced battery cell voltages can reduce storage capacities and may cause explosions or fires in the worst case which is a major obstacle for safe and optimum operations of battery-driven appliances, such as EVs. Therefore, battery cell voltage equalizations have become an important research topic. Many studies have been conducted to develop and improve techniques to equalize battery cell voltages by incorporating various remarkable features. This study makes a comprehensive and systematic review of these cell equalization techniques. The importance and research prospect of battery cell voltage equalizers are discussed. A critical analysis of recent techniques, particularly on construction, operation, and control strategy of equalization circuits, is also presented. Moreover, recent studies are compared based on circuit designs, sizes, costs, complexities, system efficiencies, applications, control strategies, balancing speeds, and voltage/current stresses of different equalizers. Commonly used two different types of control strategies/algorithms in software system of battery cell equalizers are briefly described. The recent research trend of different equalizers is also discussed in detail. Simulation results of few equalization approaches and performance evaluation techniques are analyzed. Highlights: Detailed review focusing on existing battery cells voltage equalizers circuits are presented. Operating principle, primary features, and limitations of different battery cells voltage equalizers are summarized. Categories of control strategies/algorithms used in software system of battery cells voltage equalizers are overviewed. Recent research trend of equalizers for battery cells equalization are explained. Four distinctive battery cells voltage equalizer circuits are simulated utilizing MATLAB/Simulink and compared.